Profile and follow-up of patients with tuberculosis in a priority city in Brazil - Pereira,Jisleny da Cruz (2015)
OBJECTIVE To analyze the cases of tuberculosis and the impact of direct follow-up on the assessment of treatment outcomes.METHODS This open prospective cohort study evaluated 504 cases of tuberculosis reported in the Sistema de Informação de Agravos de Notificação (SINAN – Notifiable Diseases Information System) in Juiz de Fora, MG, Southeastern Brazil, between 2008 and 2009. The incidence of treatment outcomes was compared between a group of patients diagnosed with tuberculosis and directly followed up by monthly consultations during return visits (287) and a patient group for which the information was indirectly collected (217) through the city’s surveillance system. The Chi-square test was used to compare the percentages, with a significance level of 0.05. The relative risk (RR) was used to evaluate the differences in the incidence rate of each type of treatment outcome between the two groups.RESULTS Of the outcomes directly and indirectly evaluated, 18.5% and 3.2% corresponded to treatment default and 3.8% and 0.5% corresponded to treatment failure, respectively. The incidence of treatment default and failure was higher in the group with direct follow-up (p < 0.05) (RR = 5.72, 95%CI 2.65;12.34, and RR = 8.31, 95%CI 1.08;63.92, respectively).CONCLUSIONS A higher incidence of treatment default and failure was observed in the directly followed up group, and most of these cases were neglected by the disease reporting system. Therefore, effective measures are needed to improve the control of tuberculosis and data quality.